2018
DOI: 10.3390/e20020127
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multiscale Entropy in Assessing Plantar Skin Blood Flow Dynamics in Diabetics with Peripheral Neuropathy

Abstract: Diabetic foot ulcer (DFU) is a common complication of diabetes mellitus, while tissue ischemia caused by impaired vasodilatory response to plantar pressure is thought to be a major factor of the development of DFUs, which has been assessed using various measures of skin blood flow (SBF) in the time or frequency domain. These measures, however, are incapable of characterizing nonlinear dynamics of SBF, which is an indicator of pathologic alterations of microcirculation in the diabetic foot. This study recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…However, wavelet-based spectrum is incapable of characterizing nonlinear properties of blood flow oscillations (BFO), which are structural properties rather than the magnitude of variability [ 12 ]. It has been demonstrated that nonlinear properties of BFO could be a critical aspect for assessing SBF regulation and altered nonlinear properties of BFO are associated with microvascular dysfunction [ 13 , 14 , 15 , 16 , 17 , 18 ]. In our previous study [ 17 ], we investigated SBF responses at the first metatarsal head of diabetics and healthy controls induced by locally applied pressure and heating.…”
Section: Introductionmentioning
confidence: 99%
“…However, wavelet-based spectrum is incapable of characterizing nonlinear properties of blood flow oscillations (BFO), which are structural properties rather than the magnitude of variability [ 12 ]. It has been demonstrated that nonlinear properties of BFO could be a critical aspect for assessing SBF regulation and altered nonlinear properties of BFO are associated with microvascular dysfunction [ 13 , 14 , 15 , 16 , 17 , 18 ]. In our previous study [ 17 ], we investigated SBF responses at the first metatarsal head of diabetics and healthy controls induced by locally applied pressure and heating.…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al 24 In recent decades, due to the ability to evaluate the complexity of the system, various entropy algorithms, such as Shannon entropy, 26 sample entropy, 27 approximate entropy, 28 and fuzzy entropy, 29 have been widely used to judge the degree of system disorder in thermodynamics, information science, and other fields. 34 However, MSE's application effect on battery fault diagnosis/prognosis, especially for real vehicles, remains to be verified. Wang et al 30 proposed a modified Shannon entropy to detect voltage fault of battery systems, which can predict the voltage fault in time through monitoring battery voltage during actual vehicular operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been widely used in the analysis of signals such as biology, brain electricity, and mechanical faults. 34 However, MSE's application effect on battery fault diagnosis/prognosis, especially for real vehicles, remains to be verified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the biomedical field, Liao et al used multiscale entropy to study complexity of skin blood flow in type 2 diabetic patients with peripheral neuropathy and in healthy controls [ 2 ]. Skin blood flow was recorded at the first metatarsal head using laser Doppler flowmetry in response to locally applied pressure and heating.…”
Section: Applications Of Sample Entropy or Its Derivativementioning
confidence: 99%